Correction: Chitosan supported silver nanowires as a platform for direct electrochemistry and highly sensitive electrochemical glucose biosensing. Issue 27 (29th February 2016) - Kumar-Krishnan, Siva; Chakaravarthy, S.; Hernandez-Rangel, A.; Prokhorov, E.; Luna-Bárcenas, G.; Esparza, Rodrigo; Meyyappan, M.
Abstract : Correction for 'Chitosan supported silver nanowires as a platform for direct electrochemistry and highly sensitive electrochemical glucose biosensing' by Siva Kumar-Krishnan et al., RSC Adv., 2016, 6, 20102–20108.